2015
DOI: 10.1002/ptr.5552
|View full text |Cite
|
Sign up to set email alerts
|

Binary and Tertiary Mixtures of Satureja hortensis and Origanum vulgare Essential Oils as Potent Antimicrobial Agents Against Helicobacter pylori

Abstract: Essential oils possess strong antimicrobial activity, even against multiresistant Helicobacter pylori. Available therapies against H. pylori infection have multiple disadvantages, indicating a great need for a development of new therapeutics. The purpose of this study was to develop a potent natural product based anti-H. pylori formulation. First, anti-H. pylori activity of nine essential oils was determined, after which the most active oils were mixed in various ratios for further testing. Satureja hortensis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 29 publications
1
22
0
2
Order By: Relevance
“…Due to the flavoring and antimicrobial activities, in particular, CV has been proposed as a natural food preservative for the food industry (Daferera, Ziogas, & Polissiou, ; Solórzano‐Santos & Miranda‐Novales, ; Salehi, Mishra, et al, 2018). In addition, CV, as a main constituent of plant extracts derived from Zataria multiflora Boiss, Satureja hortensis , and O. vulgare , improves the immune response (Boskabady & Gholami Mahtaj, ; Boskabady & Jalali, ; Boskabady, Tabatabaee, & Jalali, ; Khazdair, Ghorani, Alavinezhad, & Boskabady, ), mediating the antimicrobial, antioxidant, anti‐inflammatory, and anticancer properties of these plants (Burt et al, ; Fitsiou et al, ; Hashemipour et al, ; Kim, Lillehoj, Lee, Jang, & Bravo, ; Lesjak et al, ; Mahtaj, Feizpour, Kianmehr, Soukhtanloo, & Boskabady, ; Ocaña‐Fuentes, Arranz‐Gutiérrez, Señorans, & Reglero, ; Rajput et al, ; Silva et al, ). The major aim of this review was to provide the most updated evidence, including clinical trials, of CV in human health, with a focus on its pharmacokinetics and safety profile and antibacterial, antioxidant, and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the flavoring and antimicrobial activities, in particular, CV has been proposed as a natural food preservative for the food industry (Daferera, Ziogas, & Polissiou, ; Solórzano‐Santos & Miranda‐Novales, ; Salehi, Mishra, et al, 2018). In addition, CV, as a main constituent of plant extracts derived from Zataria multiflora Boiss, Satureja hortensis , and O. vulgare , improves the immune response (Boskabady & Gholami Mahtaj, ; Boskabady & Jalali, ; Boskabady, Tabatabaee, & Jalali, ; Khazdair, Ghorani, Alavinezhad, & Boskabady, ), mediating the antimicrobial, antioxidant, anti‐inflammatory, and anticancer properties of these plants (Burt et al, ; Fitsiou et al, ; Hashemipour et al, ; Kim, Lillehoj, Lee, Jang, & Bravo, ; Lesjak et al, ; Mahtaj, Feizpour, Kianmehr, Soukhtanloo, & Boskabady, ; Ocaña‐Fuentes, Arranz‐Gutiérrez, Señorans, & Reglero, ; Rajput et al, ; Silva et al, ). The major aim of this review was to provide the most updated evidence, including clinical trials, of CV in human health, with a focus on its pharmacokinetics and safety profile and antibacterial, antioxidant, and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…This study primarily aimed to investigate the in vivo anti‐ H. pylori effect of the 2:1 mixture of S. hortensis and O. vulgare subsp. hirtum essential oils (2MIX), as our previous in vitro results demonstrated that this essential oil mixture would be a highly effective therapeutic agent against H. pylori …”
Section: Discussionmentioning
confidence: 99%
“…Essential oils were prepared as described previously . Briefly, the plant material of S. hortensis and O. vulgare subsp.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations